Optimization of temperature parameters for screening unexpected antibodies in Rh system by manual polybrene test - ZOU Xin; CHEN Minjie; MA Sifei; YANG Hongmei (Zhongguo shuxue zazhi, 2025)
[Objective] To explore the temperature parameters affecting the polybrene test and determine the optimal temperature conditions for detecting unexpected antibodies of the Rh system. [Methods] The reaction of IgG human anti-D antibody with different dilutions (undiluted, 1∶2, 1∶4, 1∶8, 1∶16, 1∶32，1∶64) with D antigen-positive red blood cells was detected by manual polybrene test (MPT). Different temperatures (25℃ and 37℃) were set, and the reaction time with low ionic medium was 4 minutes. The agglutination integral value of anti-D and red cell depolymerization time were compared to observe the effect of enhanced agglutination reaction, thereby establishing the test temperature reaction conditions for enhancing the MPT. The same reaction condition was applied to 36 blood samples containing unexpected antibodies of the Rh system, and the effect of enhanced MPT was observed in comparison with the polybrene method and the antiglobulin test (column agglutination). [Results] With all other conditions held constant, when low ionic medium was added, the incubation temperature of 25℃ and 37℃ resulted in different total agglutination integral values for anti-D (20.9±2.025 vs 25.5±2.635), and the comparison showed a significant difference (P<0.05). When the antibody dilution was 1∶16, the incubation temperature of 25℃ and 37℃ resulted in different agglutination integral values (3.9±0.738 vs 5.8±0.632), and the comparison showed a significant difference (P<0.05). Erythrocyte depolymerization time (62.8±8.149 vs 90.1±10.713) was significantly different (P<0.05). At a dilution of 1∶32, the incubation temperatures of 25℃ and 37℃ resulted in different agglutination integral values (2.5±0.527 vs 4.3±0.675), as well as different red blood cell dissociation times (35.4±7.792 vs 57.4±10.885)(P<0.05), and the comparison showed a significant difference (P<0.05), with no differences observed in the other groups. In the detection of 36 Rh system unexpected antibody samples, when the antibody titer was ≤2, the enhanced polybrene method had a higher positive rate, and when the antibody titer was ≥4, the detection rates of the three methods were consistent. [Conclusion] The reference temperature condition for the modified MPT is incubation at 37℃ for 4 min after the addition of low ionic medium. The application of this temperature condition to unexpected antibody samples of Rh system could achieve a significant enhancement effect, thereby increasing transfusion safety for the treatment of emergency patients, and is worth popularizing.